Budidaya Burung Hantu Di Desa Pasi Lamongan Sebagai Predator Tikus Sawah Dalam Mensiasati Ketahanan Pangan - Waloyu, Minto; Novita Sari, Rizqi; Islami, Mega Cattleya P. A. (EDUPEDIA Publisher, 2023)
AbstractEfforts to increase food production in rice and polowijo are often constrained by pests and diseases. One of them is rat pests as rodents. Owls are a solution for handling rat pests. Owl cultivation requires the cost of making pegupon as a house for owls with prices ranging from Rp. 750,000.00 to Rp. 1,500,000.00. The price depends on the material used. Meanwhile, Pasi village already has 10 owls with more than 50 owls. The development of owls knows no season, this is comparable to the rapid development of mice. So that owls can prey on as many as 3 to 7 rats every day, at least the number of rat pests can be significantly reduced when compared to their growth. Keywords: Rat Pests, Owl Breeding, Owl Nests